(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Spiritual–moral education is a continuous process aimed at gradually forming in a person high moral convictions, patriotism, humanity and a sense of beauty, as well as loyalty to national and universal values, with the goal of raising a spiritually mature, harmoniously developed individual. This article discusses the reasons for the growing need for spiritual–moral education in a globalized world, the impact of globalization on the spirituality of youth, the threats of “mass culture” and the digital environment, and the ways of forming spiritual immunity.